P06.08 Immunomodulatory biomarkers in neoadjuvant chemotherapy of breast cancer. (1st October 2020) - Wimmer, K; Sachet, M; Exner, R; Fitzal, F; Filipits, M; Oehler, R
Abstract : Background: Neoadjuvant chemotherapy (NAC) with epirubicin/cyclophosphamid followed by docetaxel (E/C->D) is currently one standard-of-care therapy option in women with early, high-risk or locally advanced breast cancer. While some patients respond excellently to preoperative therapy, in other patients significant tumor shrinkage cannot be achieved. We investigated the impact of NAC on circulating immunomodulatory parameters. We also examined whether changes in these parameters correlate with the response to NAC measured by the Residual Cancer Burden (RCB) score determined after neoadjuvant treatment. Materials and Methods: To detect drug-specific effects, two different NAC regimens in primary breast cancer patients scheduled to pre-operative therapy were compared. 39 patients with conventional anthracycline/taxane sequence (E/C->D, n=39) and 40 patients with reverse sequence (D->E/C) were included. Blood plasma samples were collected at three time points - 'baseline' (before NAC), 'midterm' (after the first six cycles of NAC) and 'surgery' (after NAC before operation). The plasma levels of uPA, uPAR, TIM-3, MCP-1, MCP-2, OPG, IP-10, CD 27, Eotaxin, Tweak, TRAIL, PD-L2, M-CSF and VEGF-A were determined either by using ELISA or a multiplex bead array immunoassay. Results: OPG, CD27, MCP-1, MCP-2, CCl19, Tweak, TRAIL, PD-L2 and M-CSF decreased between baseline and midterm in E/D->D patients. However, the majority of patients treated with the reverse sequence showed no such effect. These drug-induced changes correlated with the RCB score. Non-responders (RCB ≥ 1.36) showed a significantly different pattern than responders. Conclusion: These data confirm that NAC affects the immune system in a drug-specific manner. Factors correlating with the RCB-score might represent promising biomarkers to predict the response to therapy. Disclosure Information: K. Wimmer: None. M. Sachet: None. R. Exner: None. F. Fitzal: None. M. Filipits: None. R. Oehler: None.